Improving Student Achievement in Islamic Religious Education Subjects with the Basic Material of Organizing the Corpse through the Gallery Walk and Simulation Methods in Class XI IPS 1 SMA Negeri 1 Jatibarang Odd Semester 2016/2017 Academic Year - Syamsu (Journal of Educational Analytics, 2023)
This study aims to determine the increase in activity and learning achievement of students in learning Islamic Religious Education and Moral Character, the subject matter of Procedures for Carrying Out Bodies, by applying the gallery walk and simulation methods. This research uses action studies (action research). This research was carried out in three stages: the pre-cycle stage, cycle 1, and cycle 2. In the pre-cycle learning activity stage, students had a percentage of 61.43% and an average final score of 63.90. In cycle 1, after the act of active learning, students increased to 68.58%, and the average final test was 68.90. Whereas in cycle 2, after the evaluation of the implementation of the action in cycle 2, the learning activity experienced an increase, namely the activeness of students increased by 78.58%, and the average student final test was 74.76. From these three stages, it is clear that there has been an increase after the gallery walk and simulation methods were applied compared to before.